UJI KELARUTAN UNTUK SELEKSI FASE MINYAK, SURFAKTAN DAN KOSURFAKTAN DALAM PREPARASI SELF-NANO EMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) FUROSEMID - lis Wahyuningsih; Sugiyanto Sugiyanto; Yuswanto Yuswanto; Ronny Martein (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Furosemide has a low solubility in water and leads to absorption profile this drug is highly variable after oral administration. Self-nano emulsifying drug delivery system (SNEDDS) is a drug delivery system that can be developed for furosemide to improve its absorption profile. Selection of oil phase, surfactant and cosurfactant has an important role in furosemide SNEDDS. The solubility of furosemide performed in the oil phase: oleic acid, red palm oil, and olive oil. The solubility of furosemide was also measured in a surfactant: tween 80, tween 20 and cremophor RH40 and the cosurfactant: propilenglikol (PG), polyethylene glycol (PEG) 400 and glycerol. The solubility test was performed at a temperature of 37°C and furosemide levels in the oil phase, surfactant and cosurfactant were determined by a spectrophotometer. Furosemide solubility in the oil phase of oleic acid, red palm oil, and olive oil are (158, 80 and 32) mg/mL respectively. Meanwhile, furosemide solubility in surfactant tween 80, tween 20 and cremophor RH40 are (278.889; 202.527 and 237.250) mg/mL respectively. In addition, the solubility of furosemide in a cosurfactant PG, PEG 400 and glycerol are (92.0; 1374.867 and 225.044) mg/mL respectively. This study concluded that the greatest furosemide solubility in the oil phase, surfactant and cosurfactant respectively is oleic acid, tween 80 and PEG 400. These materials can be selected as a component of furosemide SNEDDS. Key words: furosemide, SNEDDS, oil phase, surfactant, cosurfactant